OPTIMASI TEKNIK STEGANOGRAFI AMELSBR PADA EMPAT BIT TERAKHIR DENGAN COVER IMAGE BERWARNA - Muhammad Alfin Fikri; F. X. Ferdinandus (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
The dynamic growth of data transmission in the modern age needs a safe interchange of data. Usually, the answer is between steganography and cryptography. Steganography is a well-established technique for protecting hidden data from unauthorized access into a cover object in such a fashion that it is easily imperceptible to human eyes. Purpose: This work proposes an optimization towards Adaptive Minimum Error Least Significant Bit Replacement (AMELSBR) by modifying at least four bits to be replaced. Sadly, steganography is often detectable by human eyes, especially if underwent such bit replacement modification. To solve this problem, we have since optimized AMELSBR. Method: Specifically, we optimized AMELSBR so it can use the last 4 bit in cover image. We divided the experiment scheme based on per replaced bit, namely one bit, two bits, three bits, and four bits. The object covered in this work is colored images, divided into four classes: abstract images, landscape images, animal images, and fruit images.. Results: We were able to minimize Mean Squared Error into at least 1 and Peak-to-Signal Ratio into at least under 35 dB in this work. We also tested the stego images as the end result of the AMELSBR steganography process using brightness, contrast, resize, noise, and blur. Conclusion: Our experiment proves that the optimized AMELSBR as steganography technique can be reliable for text embedding in the cover image without using cryptography as intended in standard use.